The Ultimate Art of War : A Step-by-Step Illustrated Guide to Sun Tzu's Teachings - Cummins, Antony (London Watkins, 2019)
Composed in the 5th century BC, Sun Tzu's Art of War is the earliest-known treatise on military strategy, and is still hugely popular around the world for its perceptive tactical advice to commanders on how to win at war with minimal bloodshed. Aimed at all those who want to study the text in depth, this is the first step-by-step guide to the famous treatise, breaking down the 13 chapters of the original into 200 easily digested lessons, from 'do not press a desperate enemy' to 'control your troops through bond of loyalty' to 'when you are weak, beware attack', all accompanied by comprehensive commentary and clarified with around 250 illustrations. Making the lessons even more memorable and easy to understand, the black/red illustrations include strategic diagrams, evocative line drawings and beautiful calligraphy. This ultimate guide to Art of War includes the classic 1910 translation by Lionel Giles and commentary that takes into account all academic interpretations of the text, highlighting differences between modern translations as well as the perspectives of historical Chinese commentators. No other edition compares and contrasts the viewpoints of different contemporary translators, or explains exactly what each section of this often enigmatic text actually means
Include Illustrations and Index
Keywords: Pictorial works. -- Military art and science -- China -- Sunzi bing fa (Sunzi) -- Business -- War -- Early works to 1800. -- Military art and science